Breaking down the cellular responses to type I interferon neurotoxicity in the brain - Viengkhou, Barney; Hofer, Markus J. (Frontiers in Immunology, 2023)
Since their original discovery, type I interferons (IFN-Is) have been closely associated with anti-viral immune responses. However, their biological functions are much broader and more complex. Recent findings have uncovered a darker side of IFN-Is, where chronically elevated levels induce disease. The underlying causes of these 'interferonopathies' are diverse and include monogenetic syndromes, autoimmune disorders as well as chronic infections. Importantly, the interferonopathies often manifest in the central nervous system (CNS) where they cause devastating neuroinflammatory and neurodegenerative pathologies. The prominent involvement of the CNS in these disorders indicates a particular susceptibility of brain cells to IFN-I toxicity, whose basis we have just recently begun to unravel. Yet, understanding the nature of IFN-I neurotoxicity is a crucial first step for the development of therapeutic strategies to treat patients. Here we will discuss the current knowledge of how IFN-Is mediate neurotoxicity in the brain.